Introduction to carpentry - Sankara Rao, Dr. Lakkoju (Main Workshop, IIT (BHU), Varanasi, 2016)
This video helps the students to understand the step by step procedure to prepare T-bridle joint in the carpentry shop.
This video helps the students to understand the step by step procedure to prepare T-bridle joint in the carpentry shop
Keywords: carpentry; T-bridle joint